Coping with Falling Oil Prices : The Different Fortunes of African Banks - Gueye, Cheikh (IMF Working Papers; Working Paper ;, 2019)
This paper studies the impact of declining oil prices on banks in sub-Saharan African oil-exporting countries. Results indicate that banks respond differently to an oil shock depending on their ownership: (i) domestic banks are the most adversely impacted and experience a deterioration in asset quality and liquidity; (ii) foreign-owned banks are the most resilient as they are able to improve asset quality and attract deposits but at the same time, they decelerate credit growth; in contrast, (iii) Pan-African Banks help stabilize overall credit but large banks in that segment experience reduced asset quality. These differentiated results suggest a tradeoff between maintaining credit growth and safeguarding financial stability in an oil slump which could be addressed by both micro- and macroprudential policies.